Users’ Perception of the Hospital Information System in a Maternity Hospital in Lampung, Indonesia - Asyary, Al; Prasetyo, Arief Kurniawan Nur; Eryando, Tris; Gerke, Solvay (UI Scholars Hub, 2019)
Hospital information systems (HIS) have been applied on a massive scale; however, user evaluation of their effectiveness, efficiency, and service quality improvements remain rare. This study aimed to describe the utility of information systems from the users’ point of view by using the Technology Acceptance Model (TAM) in a maternity hospital in Lampung, Indonesia. The study provided an overview of the features of the information system and the workflow of the user through this information system. Screenshots were taken by using Camtasia Studio 2.0 Trial Version application software for one day (two shifts) in the outpatient service. The HIS generally supported the workflow, but not all application modules were fully applied. The obstacles appear to be at the registration unit/outpatient registration and queue dashboard, cashier unit, pharmacy unit, medicine storage/room, and poly unit/checking room. A TAM framework, which included perceived ease of use and perceived usefulness of the information system, revealed that the currently implemented HIS was not perceived as optimal. However, users are still optimistic and aware of the usefulness of the information system in supporting their jobs. Thus, leaders have committed to initiate the potential development of this information system in the inpatient polyclinic.